Factors Associated with the Incidence of Tuberculosis (TB) in Children and Stunting - Indayah Dewi Tunggal; Ayun Sriatmi; Martini Martini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tuberculosis (TB) and stunting are major health problems affecting children, particularly in developing countries. This study aims to analyze the factors associated with the incidence of TB and stunting among children in Pekalongan City. A cross-sectional study was conducted involving children diagnosed with TB and those experiencing stunting. The population in this study includes all toddlers in Pekalongan City in the year 2024, totaling 18,992 individuals. The sample consists of toddlers residing in Pekalongan City who meet specific inclusion and exclusion criteria. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in a total of 100 respondents. Inclusion criteria include toddlers aged 6–59 months, those living in Pekalongan City, and those who possess a Maternal and Child Health (KIA) book. Exclusion criteria include toddlers with chronic illnesses other than tuberculosis (TB) and those whose parents could not be reached at home. The sampling technique used was proportional random sampling, which ensures each unit has a chance to be selected proportionally based on the population distribution. This method increases representativeness and minimizes variability within the sample. Data were collected through structured interviews, medical records, and anthropometric measurements. Statistical analysis was performed using the chi-square test and logistic regression to identify significant factors. The results indicate that nutritional status, household economic conditions, history of TB contact, and immunization status are significantly associated with TB incidence in children. Additionally, maternal education level, dietary intake, and recurrent infections are key determinants of stunting. Children with a history of TB exposure and poor nutritional intake had a higher risk of developing stunting. The findings highlight the need for integrated health interventions focusing on nutrition improvement, early TB detection, and enhanced public health education to mitigate both TB and stunting in children.